Pelatihan Literasi Digital Pada Ibu – Ibu Rumah Tangga Di Dusun Bendungan Desa Banjarejo - Muhammad David; Heti Nur Ani; Ardiansyah Ahsanul Hayat; Abdul Rozaq Alfarizi; Saras Dewi Qomariyah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
This community service is carried out to increase the literacy of housewives in using social media and to extract bijad information provided by social media, as well as provide training on how to use smartphones to housewives who do not know how to use smartphones. This service was attended by 38 participants and divided into three stages, the first of which was preparation, The second is the implementation and the third is evaluation, from the results of the service that has been done by housewives in Damungan Hamlet, Banjarejo Village, Kedungpring District, Lamongan Regency.